P543 Higher post-induction infliximab serum trough levels are associated with healing of fistulising perianal Crohn's disease in children. (16th January 2018) - El-Matary, W; Walters, T; Huynh, H; deBruyn, J; Mack, D; Jacobson, K; Sherlock, M; Church, P; Wine, E; Carroll, M; Benchimol, E; Lawrence, S; et al.
Abstract: Background: There are no data regarding the association of response of fistulising perianal Crohn's disease (PCD) with serum infliximab (IFX) levels in children. In a multi-centre national inception cohort using prospectively collected data, we aimed to determine serum trough IFX levels at starting maintenance (pre-dose 4) that are associated with healing of fistulising PCD at Week 24. Methods: The Canadian Children IBD Network brings together 12 academic paediatric IBD centres from across Canada. Patients younger than 17 years of age presenting with new-onset IBD were enrolled in an inception cohort study. Baseline and longitudinal phenotypic data were prospectively collected using standardised forms, which included a "perianal disease report form". Consecutive children with fistulising PCD identified via clinical and/or magnetic resonance pelvic examination and treated with IFX between April 2013 and June 2017 and had IFX trough pre-dose 4 levels measured were included in the study. Response was defined as cessation or significant improvement of fistula drainage as defined by physician assessment. Correlation between IFX levels and response of fistulising PCD at Week 24 was examined using Pearson correlation analysis. Area under the receiver-operating characteristic curve (AUROC) was determined, with sensitivity and specificity calculated for the best cut-off of IFX level. Results: A total of 667 children with Crohn's disease were recruited with 85 (12.7%) patients diagnosed with fistulising PCD. Twenty-seven (mean age 12.5 + 5.1 years, 63% males) of 52 (52%) children with fistulising PCD on IFX had their pre-dose 4 IFX trough levels measured. All patients received three induction doses (median 6 mg/kg) of IFX at 0, 2, 6 weeks with dose 4 given at a median time interval from dose 3 of 50 days. At Week 24, 14 of 27 (52%) patients were classified as respondents with healing/healed PCD while the rest had on-going active fistulising PCD. The median IFX trough pre-dose four level in the respondents was 12.7 μg/ml (interquartile range (IQR) = 6.6–15.5) compared with 5.4 μg/ml (IQR = 2.7–8.4) in the active disease group ( p = 0.02). There was a strong correlation between IFX level and healing of fistulising PCD at Week 24 ( r = 0.65, p < 0.001). AUROC was 0.80 (95% confidence interval 0.64–0.97, p = 0.007) for pre-dose four level to predict response of fistulising PCD at Week 24, and a level of 12.7 μg/ml predicted fistula healing at Week 24 with sensitivity 0.62 and specificity 0.65. Conclusions: Following induction phase, higher trough IFX levels are associated with a better outcome for fistulising PCD in children. Our results need to be confirmed in larger prospective studies that include measurements of IFX levels and antibodies during the induction phase.